2012
DOI: 10.1021/es300303f
|View full text |Cite
|
Sign up to set email alerts
|

Magnetic Nanoscaled Fe3O4/CeO2 Composite as an Efficient Fenton-Like Heterogeneous Catalyst for Degradation of 4-Chlorophenol

Abstract: Magnetic nanoscaled Fe(3)O(4)/CeO(2) composite was prepared by the impregnation method and characterized as a heterogeneous Fenton-like catalyst for 4-chlorophenol (4-CP) degradation. The catalytic activity was evaluated in view of the effects of various processes, pH value, catalyst addition, hydrogen peroxide (H(2)O(2)) concentration, and temperature, and the pseudo-first-order kinetic constant of 0.11 min(-1) was obtained for 4-CP degradation at 30 °C and pH 3.0 with 30 mM H(2)O(2), 2.0 g L(-1) Fe(3)O(4)/Ce… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

8
341
1

Year Published

2014
2014
2024
2024

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 1,029 publications
(350 citation statements)
references
References 52 publications
8
341
1
Order By: Relevance
“…The 4-CP removal can reach about 100% within 30, 60, and 120 min at the PMS concentration of 0.8 mM, 0.4 mM, and 0.15 mM, respectively. Further increasing the PMS concentration did not increase the degradation efficiency but resulted in a slight inhibition perhaps due to the self-quenching of SO 4 •− by excess PMS. 34 Meanwhile, neutral or alkalescent initial pH conditions exhibit a slightly superior 4-CP removal performance than acidic conditions ( Figure S7b) in this reaction process.…”
Section: ■ Introductionmentioning
confidence: 87%
See 2 more Smart Citations
“…The 4-CP removal can reach about 100% within 30, 60, and 120 min at the PMS concentration of 0.8 mM, 0.4 mM, and 0.15 mM, respectively. Further increasing the PMS concentration did not increase the degradation efficiency but resulted in a slight inhibition perhaps due to the self-quenching of SO 4 •− by excess PMS. 34 Meanwhile, neutral or alkalescent initial pH conditions exhibit a slightly superior 4-CP removal performance than acidic conditions ( Figure S7b) in this reaction process.…”
Section: ■ Introductionmentioning
confidence: 87%
“…8,9 For SO 4 •− production, the combination of transition metal ions with peroxymonosulfate (PMS) is highly efficient, and cobalt ions have been found to be the best activator in this system. 10 While considering the disadvantages of homogeneous process associated with the precipitation of metal salts and the difficulty in catalyst recycling, researchers deflect to develop heterogeneous cobalt based catalysts.…”
Section: ■ Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…That was mainly attributed to iron leaching (≈1 mg L -1 ). Xu and Wang (2012b) [108] also found a loss of activity upon 6 runs (from 100% to 40% conversion for 1 st to 6 th runs, respectively) in In contrast to the relatively low stability of some nanocomposites, Niu et al (2011) [110] demonstrated that humic acid-coated MNPs present a remarkable stability in CWPO of sulfathiazole, maintaining complete conversion upon 3 successive runs. However, these authors did not provide information about TOC reduction upon sequential cycles.…”
Section: Supported Ferromagnetic Nanoparticles and Magnetic Compositesmentioning
confidence: 98%
“…On the basis of the observations from previous studies [24][25][26]39 and the above study, the reaction mechanism may consist of a dominant digestion and a subsidiary digestion, which have occurred on the surface of MNPs and in the leaching solution, respectively. Figure 1A,B shows that the mixture can be digested to some extent in the 30,80, and 120 nm were tested to digest the milk mixture under the same experimental conditions, as shown in Figure 2.…”
Section: ■ Results and Discussionmentioning
confidence: 74%